2004
DOI: 10.3200/mono.130.4.277-306
|View full text |Cite
|
Sign up to set email alerts
|

Self-Construals and Values in Different Cultural and Socioeconomic Contexts

Abstract: In this study the authors investigated (a) how individuational and relational self-orientations, as well as self-directed and other-directed values, are related to one another, and (b) how these self- and value orientations differ across 2 cultural (i.e., 422 Turkish and 441 American university students) and 2 socioeconomic status (SES) groups (i.e., 186 lower SES and 167 upper SES Turkish high school students). Across cross-cultural and SES groups, individuational and relational self-orientations appeared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 40 publications
7
40
0
3
Order By: Relevance
“…However, Turkey has been undergoing rapid social and economic change. Especially since the 1980s, people from the more progressive segments of society have shown more individualism in their values, but without a significant decline in relatedness (Imamog˘lu and Karakitapog˘lu-Aygu¨n, 2004;Karakitapog˘lu-Aygu¨n, 2004). Accordingly, close relationships between leaders and followers and paternalistic features of leaders are still expected to be prevalent in the Turkish business context.…”
Section: Introductionmentioning
confidence: 99%
“…However, Turkey has been undergoing rapid social and economic change. Especially since the 1980s, people from the more progressive segments of society have shown more individualism in their values, but without a significant decline in relatedness (Imamog˘lu and Karakitapog˘lu-Aygu¨n, 2004;Karakitapog˘lu-Aygu¨n, 2004). Accordingly, close relationships between leaders and followers and paternalistic features of leaders are still expected to be prevalent in the Turkish business context.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individuation and relatedness, as considered by the BID model, should not be equated with I-C, respectively, because the latter dimensions refer to highly global constructs of world views, encompassing multiple components (Oyserman, Coon, & Kemmelmeier, 2002). Although not equivalent, individuation may be expected to be associated with those components of individualism that focus on reliance on internal referents (but not in terms of being separate), whereas relatedness may be considered to be associated with those aspects of collectivism concerned with being related with others and valuing affectionate ties with family and significant others (but not being conforming or group bound), as suggested by recent studies (Imamoglu & Karakitapoglu-Aygün, 2004;Imamoglu & Kurt, unpubl. data, 2004).…”
Section: Balanced Integration and Differentiation Modelmentioning
confidence: 95%
“…However, a theoretical discussion of those different outlooks is beyond the limits of this paper (see Imamoglu, 2003;also Markus & Kitayama, 2003;Miller, 2003; for related reviews). Also, in direct tests of the model by using the BID scale, which is described later in the paper, investigators have demonstrated that individuation and relatedness are distinct orientations, and have demonstrated the existence of four distinct self-types among Turkish, American, and Canadian samples (Imamoglu, 1998(Imamoglu, , 2003(Imamoglu, , 2006Kurt, 2002a,b;Gezici & Güvenç, 2003;Güler, 2004;Imamoglu & Karakitapoglu-Aygün, 2004, 2006Imamoglu, 2005). Furthermore, as predicted by the model, relatedness and individuation were found to be associated with qualitatively distinct and complementary domains of variables (e.g.…”
Section: Balanced Integration and Differentiation Modelmentioning
confidence: 99%
“…Volume 3 / Issue 2 / studies in Turkey only involved adolescence, young adulthood and adulthood (Dirilen, 2006;Gümüş, 2009;İmamoğlu & Katipoğlu-Akgün, 2004;Yılmaz, Avşaroğlu & Deniz, 2010).Values develop in earlier years of children, thus there is need to learn about values starting from middle childhood period and a scale that will measure these values. The existance of such a scale will provide to make new researches.…”
Section: Wwwijerecommentioning
confidence: 99%